Four new species of Contulma from South America (Trichoptera: Anomalopsychidae) - Holzenthal, Ralph W.; Robertson, Desiree R. (Zootaxa, 2006)
Four new species in the caddisfly genus Contulma Flint 1969 (Trichoptera: Anomalopsychidae) are described from Bolivia and southeastern Brazil: C. boliviensis n. sp. (Bolivia), C. fluminensis n. sp. (Brazil), C. meloi n. sp. (Brazil), and C. tripui n. sp. (Brazil). The Bolivian species represents the first record of the genus and family for Bolivia. The Brazilian species form a closely related group of species also including C. tijuca Holzenthal & Flint 1995.